Dive behaviour and respiration rates of humpback whales (Megaptera Novaeangliae) during foraging off Northern Norway, with implications for metabolic rate estimates - Gunnufsen, Rikke (UiT Norges arktiske universitet, 2022)
Knowing the metabolic rate of marine mammals is often important as baseline knowledge of their biology and physiology, e.g., to allow ecosystem assessments and estimation of their resource needs and use, and prey requirements. However, our current knowledge of energetics of large cetaceans is limited compared to many smaller cetaceans. Determining the energy expenditure of large free-ranging whales is logistically extremely difficult and we must therefore often rely on various indirect methods such as modelling heat loss, using hydrodynamic models and respiration rate as proxies for metabolic rate. In this thesis, I used pre-existing time-depth data of tagged humpback whales on their foraging ground in Northern Norway to investigate how the respiration rate is linked to different dive behaviour variables. I furthermore made some quantitative estimates of humpback whale metabolic rates based on own data on respiration rate and other available respiratory variables. Finally, I discuss and compare different approaches for estimation of energy costs of living in these mammals. I present data covering 388 h, 4721 dive cycles, collected from altogether 21 out of 36 whales. The humpback whales mainly conducted short (4.6 ± 3.1 min) and shallow dives (41 ± 32 m) with a mean respiration rate of 1.25 ± 0.62 breaths min^1. The results indicate that respiration rate is mostly affected by the degree of locomotor activity during foraging and non-foraging dives. The field metabolic rate of adult humpback whales, with an average size of 30 tonnes, was estimated to be 0.98 ± 0.29 W kg^1 which equals to 4.1 × BMR predicted by Kleiber’s equation (1975). Similar estimations were seen for other rorquals and animal groups, indicating that the humpback whales have an energy expenditure within the magnitude as seen in other animals.